Peningkatan Hasil Belajar Dribbling Sepakbola melalui Small Side Games - Kusuma, Sagita; Ridwan, Mochamad (Universitas Pendidikan Indonesia, 2018)
The purpose of this study was to determine the increase learning outcames dribbling football through small side games. This research used quasi experiment with a quantitative approach. The research design used in this study is one group pretest-posttest design. The samples are class XI-3 totaling 33 students. Results of the analysis using SPSS version 20 can be seen of the calculated value (t-count) is greater than (t-table) with significance level of 5% or 0,05 the Ha accepted and Ho rejected. Whereas the significance of (t-count) is smaller (t-table) with a significance level of 5% or 0,05 the Ho is accepted and Ha rejected. From the results obtained by value (t-count) (t-table) (7.184 2,036) with a significance level of 5% or 0,05, then the appropriate basis for a decision in paired samples test, it can be cocluded Ha accepted and Ho rejected, which means there is the increase of test result after treatment with a percentage of 31.56% in students of class XI-3 senior high school 1 Bojonegoro.Â ABSTRAKTujuan dari penelitian ini adalah untuk mengetahui apakah ada peningkatan hasil belajar dribbling sepakbola melalui small side games. Jenis penelitian ini menggunakan eksperimen semu dengan pendekatan kuantitatif. Desain penelitian yang digunakan dalam penelitian ini adalah one group pretest-posttest design. Sampel penelitian adalah kelas XI-3 yang berjumlah 33 siswa. Berdasarkan perhitungan SPSS Statistic 20 diperoleh nilai thitung t tabel (7.184 2,036) dengan taraf signifikansi 5% atau 0,05, maka sesuai dasar pengambilan keputusan dalam uji paired samples test, maka dapat disimpulkan Ha diterima dan Ho ditolak, yang artinya ada peningkatan dari hasil tes setelah pemberian treatment dengan nilai persentase sebesar 31.56% pada siswa kelas XI-3 SMA Negeri 1 Bojonegoro.Â